Booming the Vocabulary Acquisition by Using Flipped Classroom on EFL Learners’ PPA (Performance, Perception and Acceptance) - Woro Retnaningsih; Arif Nugroho; Dao Thi Hong Van; Nur Hidayah Al Amin (VELES Voices of English Language Education Society, 2022)
With the advancement of technology, today’s language teaching and learning are no longer restricted to classroom face-to-face interaction, but it is going beyond a formal classroom. Drawing on this issue, this study sheds some light on the impact of flipped learning instruction on vocabulary acquisition of English learners as a foreign language, their perception of the practices of flipped learning, and their acceptance of the use of the WhatsApp smartphone application to assist the flipped learning activities. An experimental research design was employed by involving 60 EFL learners who were assigned into flipped (N=30) and conventional (N=30) groups. Learners of the flipped group were taught in combined learning activities before the class using WhatsApp and in-class active practices on vocabulary. This study used multiple data collection sources, including pre and post-tests on English vocabulary, a self-report survey, and a Technology Acceptance Model (TAM) questionnaire. The results demonstrated that the EFL learners in the flipped group scored higher in the post-test, and significantly outperformed their counterparts in the conventional group. Moreover, the results of the self-report survey showed that the EFL learners were at a positive perception of the flipped learning environment to study English vocabulary. Furthermore, finding on the TAM questionnaire portrayed that the EFL learners acknowledged WhatsApp as a satisfactory digital platform to assist the activities of English learning through flipped classrooms. This study offers insights for teachers and curriculum developers to begin acknowledging the promising role of digital learning of English beyond the classroom.